Temperate woodland conservation and management - Lindenmayer, David; Bennett, Andrew F.; Hobbs, R. J. (Richard J.) (CSIRO Pub., 2010)
Summarises key insights in the science, management and policy arenas associated with Australian temperate woodlands.